Real-time face swapping in video sequences: Magic Mirror - Arar, N.Murat; Bekmezci, N.Kaan; Guney, Fatma; Ekenel, Hazim Kemal (IEEE, 2011)
Magic Mirror is a face swapping tool that replaces the user's face with a selected famous person's face in the database. System interacts with the user via a user interface which enables the selection of the replacement face and directly reflects the changed appearance. First, we apply a face detection mechanism to locate the face in the frame coming from the capturing device. Then, we feed the detection result to an active appearance model to get the exact shape of the face. By using extracted information, we replace the user's face with selected target face.We display output after some post processing for color and lighting adjustments.